2001
DOI: 10.1111/j.1349-7006.2001.tb01151.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatable Subsets in Cancer of Unknown Primary Origin

Abstract: The purpose of this study was to investigate the treatable subsets in cancer of unknown primary origin (CUP). Fifty patients (27 males and 23 females; median age, 53 years) with CUP diagnosed between April 1992 and June 1999 were analyzed retrospectively. Of the 50 patients, 39 received chemotherapy: platinum-based in 31, non-platinum-based in 4, and clinical trials of new agents in 4. Of the 39 patients, 13 (33.3%; 95% confidence interval: 19.1-50.2%) showed objective responses, with 4 complete responders. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Systematic analysis of treatment responses and survival results in this heterogeneous group of patients is problematic, and the optimal management of CUP has become more complex with the recognition that some patients benefit greatly from therapy (5, 13–15). Based on clinical and pathologic features, approximately 40% of patients can be categorized within subsets for which specific treatment has been defined, whereas empiric therapy is an option for the remaining patients (5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Systematic analysis of treatment responses and survival results in this heterogeneous group of patients is problematic, and the optimal management of CUP has become more complex with the recognition that some patients benefit greatly from therapy (5, 13–15). Based on clinical and pathologic features, approximately 40% of patients can be categorized within subsets for which specific treatment has been defined, whereas empiric therapy is an option for the remaining patients (5).…”
Section: Discussionmentioning
confidence: 99%
“…In the past, various antitumor therapeutic trials have had a negligible effect on survival, encouraging a nihilistic approach to these patients who are commonly stereotyped as elderly, debilitated persons with metastases at multiple visceral sites. Nevertheless, subsets of CUP patients have been identified by defining several clinical syndromes associated with a clinical response to therapy (4, 5, 13–15). Specialized pathology techniques, e.g.…”
mentioning
confidence: 99%
“…Although the histologic features of our case presented a papillary configuration and psammoma bodies in all of the surgical specimens, no primary site was found in the body or in the ovaries. Taking into account the fact that the epithelial layer of the ovary and the peritoneum share a common origin from the coelomic epithelium embryonically and that repeated elevations of the serum CA19-9 level occurred whenever metastasis had occurred in our case, it is plausible that papillary serous carcinoma of the peritoneum is an analog with ovarian carcinoma or an extraovarian primary peritoneal carcinoma [ 3 , 14 ]. Clinical experiences in treating patients with inguinal nodes metastases of female peritoneal papillary serous carcinomas have been reported infrequently and there is a lack of a standard chemotherapeutic regimen for this unusual and poor prognostic disease [ 2 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical experiences in treating patients with inguinal nodes metastases of female peritoneal papillary serous carcinomas have been reported infrequently and there is a lack of a standard chemotherapeutic regimen for this unusual and poor prognostic disease [ 2 , 15 ]. Cisplatin-based chemotherapy might be a choice in our case, given that favorable response rates [ 3 , 14 , 15 ] have been reported in female peritoneal papillary serous carcinoma cases if metastases outside the peritoneal cavity have not been present. However, we chose modified FAM, because a regimen including 5-FU, ADM and MMC have shown some valuable activity in many adenocarcinomas of the gastrointestinal tract, pancreas, lung and breast, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Sumi et al retrospectively studied 50 patients to determine treatable subsets in the cancer of unknown primary. They concluded that patients with poorly differentiated carcinomas in whom beta-HCG was elevated and female patients with peritoneal adenocarcinomatosis achieved high response rates with platinumbased chemotherapy, 83.3 and 80%, respectively, compared with only 15.3% in the remaining patients [84].…”
Section: Extragonadal Germ Cell Tumorsmentioning
confidence: 97%